Le séchage des mangues - Rivier, Michel (éditions Quae, 2009)
This work presents the different stages in mango processing, from fruit delivery to dried mango marketing. It includes a detailed analysis of each operation: theoretical principles, equipment required, good practice in terms of usage and hygiene, quality management, "material" yields and energy consumption, labour requirements, etc. In addition to technical advice notes, readers will find a diagram of a mango drying unit, designs for a ventilated dryer, and a production manual for use in preparing for, monitoring and assessing drying campaigns. The guide is intended for managers of small- and medium- scale firms keen to improve operations at their production units, and entrepreneurs and project leaders interested in setting up mango drying units.